(untitled) (Social Science Review, 2023)
Feature film holds a significant position in Bangladesh filmscape. However, only a few of these films are aimed at raising social and political consciousness among the audience. One such film is Dahan (Affliction), directed by Sheikh Niamat Ali in 1985. Employing the theoretical lens of the Third Cinema, this study investigates how this film contributed in social and political awareness building. Therefore, this article examines the content and stylistic features of the film and concludes with the note that by providing a few alternatives to the traditional cinema techniques, the film successfully delineated the then socio-political reality of Bangladesh characterized by inequality, injustice and intellectual bankruptcy, and sought for social and political emancipation that helps audience enhance their social and political understanding. Social Science Review, Vol. 39(1), June 2022 Page 125-140